1993
DOI: 10.1093/nar/21.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Protonated pyrimidine-purine-purine triplex

Abstract: We have studied a protonated pyrimidine-purine-purine (Py-Pu-Pu) triplex, which is formed between the d(C)nd(G)n duplex and the d(AG)m oligonucleotide as the third strand and carries the CG*A+ protonated base-triads. We have observed such an intermolecular complex between a plasmid carrying the d(C)18 d(G)18 insert and the d(AG)5 oligonucleotide without bivalent cations in 200 mM of Na+ at pH4.0. Bivalent cations additionally stabilize the complex. We propose the structures for nearly isomorphous base-triads T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…2). We speculate that, under certain conditions in vivo, this sequence might adopt an H-u3 structure (4) where a protonated A pairs to a G (35). Supporting this notion, Rooney and Moore (36) have shown that the GA32 sequence stimulated recombination to similar levels as GG32 on plasmids in mammalian cells, suggesting that cellular conditions can allow for H-DNA formation by this sequence.…”
Section: Discussionmentioning
confidence: 84%
“…2). We speculate that, under certain conditions in vivo, this sequence might adopt an H-u3 structure (4) where a protonated A pairs to a G (35). Supporting this notion, Rooney and Moore (36) have shown that the GA32 sequence stimulated recombination to similar levels as GG32 on plasmids in mammalian cells, suggesting that cellular conditions can allow for H-DNA formation by this sequence.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, protonated base triads such as C-G* A+ can be incorporated into an intermolecular pyrimidine-purine*purine triplex conformation. For example, this triad can be formed between plasmids containing a d(C)n(G)n duplex sequence and a d(AG)n oligonucleotide as the third strand, or intramolecularly on a G 10 TTAA(AG) 5 sequence in a supercoiled plasmid, forming a triplex structure containing C-G*G and C-G*A+ base triads under acid conditions, but without a requirement for bivalent cations [97]. Therefore, the formation of an *H-DNA structure is more versatile and does not require sequences containing perfect mirror symmetry.…”
Section: H-dna Conformation and Its Occurrence In Genomic Dnamentioning
confidence: 99%
“…Chemical modification with potassium permanganate has proved to be an effective approach in the investigation of unusual DNA structures, conformational transitions in DNA and the structure of DNA-protein complexes, both in vitro and in vivo (Lyamichev et al 1989;Zhang & Gralla 1989;McCarthy et al 1990;Jiang et al 1991;Kainz & Roberts 1992;Voloshin et al 1992;Chiu et al 1993;Hsieh et al 1993;Malkov et al 1993;Duncan et al 1994;Gillette et al 1994;Bennett & West 1995). KMnO 4 , like osmium tetroxide, oxidizes the 5-6 double bond of pyridine bases (T q C), leading to the loss of aromaticity.…”
Section: Discussionmentioning
confidence: 99%